The Symbol of the Spider in Spider-Man Film: Cultural Implications and Ideological Dimensions - Lazrak Yassir; El Harraki Badia; ISKANDI ISKANDI (MEDIOVA: Journal of Islamic Media Studies, 2023)
Considering their specific form, comics are types of visual art and culture that transmit a message in a more straightforward and impressive way than other types of art. For instance, films that include comics often become successful, popular and develop a cult following. In connection with this point, Spider-Man, the American superhero film, is based on comics and maintains their distinctive characteristics. The film is a true cultural reflection, revealing some of dominating values and ideologies of the American society. Basically, besides the various themes and representations of ideologies in the film, the symbol of the spider, the eight- legged arachnid along with its web, is also a crucial aspect of the film’s ideological meaning. The symbol of the spider in Spider-Man film communicates a lot of different things as it is tremendously common in Native American culture and appears in a number of myths and traditions. By adopting a semiotic analysis method, the present article seeks to demonstrate the hidden cultural implications and ideological dimensions that the spider conveys in the film Spider-Man.